The Influence of Co-Cr Thickness on The Color Parameters of Metalo-Ceramic System - Abdullah J. Mohammed (University of Mosul, College of Dentistry, 2016)
ABSTRACT Aims: The thickness of Co-Cr metal beneath the ceramic in the metalo-ceramic system can affect the color parameters. This study investigated the effect of different thicknesses of Co-Cr plate on the color parameters. Materials and method: Thirty square Co-Cr samples were made (10x10)mm length, width, respectively with varying thickness (0.3, 0.5, 1)mm, two shades (A1, A3.5) of ceramic build on the metal squares five of each thickness, and they were tested by colorimeter to measure the color parameters. Results: Mean L*value of 0.3mm metal thickness of both shades have shown a significant increase on expense of other thicknesses at (P>0.05). Conclusions: L* values were increased with the decrease in the metal thickness to a value near the opaque layer thickness, and decreased with the increase of metal thickness up to five folds of opaque layer thickness, metal thickness had no effect on the means of a*b* values.